GeoDataBase geomorfologico per acquisizione dei dati tramite tecnologie mobile (GEOmedia, 2016)
Among the creation of geomorphological maps the data collection of elementsand features is one of the most important steps. The most relevantinformation to be collected are not only their position (geolocalization) butalso their classification and properties according to the official encoding:within this context the Italian National Geologic Service (SGN) set up datacollection and data storing standards through a focused documentation,the "I Quaderni” (series III), n.4 e n.10. In this paper we describe a newsystem to collect these kind of data directly on the field through the mostcommonly used tablets and smartphones. This system is based on an ESRIGeodatabase Enterprise installed on a server, an ArcGIS Online account andthe ESRI Collector App for smartphones. Data collected by operators onthe field are directly sent to the Geodatabase on server using mobile internetconnection; data structure and format follow the national standards, so theyare ready to be added into a geomorphological map.